2022
DOI: 10.1155/2022/5500604
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of Chinese Herbal Products for Hyperthyroidism in National Health Insurance System (NHIRD) of Taiwan: A Population-Based Study

Abstract: Background. Traditional Chinese Medicine (TCM) relieves associated symptoms of hyperthyroidism such as heat intolerance, palpitations, tremor, anxiety, weight loss, increased frequency of bowel movements, and shortness of breath. However, there are no studies regarding the core prescription patterns of herbal formula and single herbs for hyperthyroidism in Taiwan. Materials and Methods. This is a retrospective, observational study using the National Health Insurance Research Database (NHIRD) in Taiwan to analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Patients aged 20 years or older with newly diagnosed hyperthyroidism were identified using validated International Classification of Diseases, Ninth Revision ( ICD-9 ) or International Statistical Classification of Diseases and Related Health Problems, Tenth Revision ( ICD-10 ) codes for hyperthyroidism. 8 , 16 , 17 , 20 , 25 The same diagnosis code had to occur twice in the inpatient or outpatient setting between 2011 and 2020 to confirm each patient’s diagnosis. Eligible codes for Graves disease, toxic nodular disease, and unspecified hyperthyroidism are listed in eTable 1 in Supplement 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Patients aged 20 years or older with newly diagnosed hyperthyroidism were identified using validated International Classification of Diseases, Ninth Revision ( ICD-9 ) or International Statistical Classification of Diseases and Related Health Problems, Tenth Revision ( ICD-10 ) codes for hyperthyroidism. 8 , 16 , 17 , 20 , 25 The same diagnosis code had to occur twice in the inpatient or outpatient setting between 2011 and 2020 to confirm each patient’s diagnosis. Eligible codes for Graves disease, toxic nodular disease, and unspecified hyperthyroidism are listed in eTable 1 in Supplement 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism of CHMs in treating hyperthyroidism has also been widely explored ( 19 ). In a population-based study in Taiwan, CHMs were reported to be used in 73% of the patients with hyperthyroidism, and Jiawei-Xiaoyao-San (JWXYS) was the most commonly chosen prescription for hyperthyroidism ( 20 ).​ Many previous clinical studies have shown that the combination of JWXYS with ATDs in the treatment of hyperthyroidism can improve clinical effectiveness or reduce the dose and side effects of ATDs, and in particular, can significantly relieve symptoms ( 21 , 22 ). Furthermore, some case reports indicate that JWXYS may be a possible alternative treatment for ATDs in the presence of contraindications ( 16 , 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%